The Effect of Leadership Style and Work Discipline on The Performance of Executive Nurses at Bhayangkara Setukpa Lemdikpol Hospital, Sukabumi City - Ede, Abdul Rahman La (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2024)
Aims: Nursing services require high performance, which can be influenced by factors such as work discipline and leadership style. The aim of this study was to analyze the effects of leadership style and work discipline on the performance of nurses at Bhayangkara Setukpa Lemdikpol Hospital in Sukabumi City. Methods: This study employed a correlational design with a cross-sectional approach. The population comprised executive nurses at Bhayangkara Setukpa Lemdikpol Hospital in Sukabumi City, with a sample size of 68 individuals selected through total sampling. Data collection was conducted using questionnaires, and the statistical analysis was performed using simple linear regression and multiple linear regression tests. Results: The results showed that there was a significant influence of leadership style (p=0.000) and work discipline (p=0.000) on the performance of executive nurses. And there is a simultaneous influence of leadership style and work discipline on the performance of executive nurses (p<0.05). Conclusion: The findings of this study indicate a simultaneous influence of leadership style and work discipline on the performance of executive nurses. To enhance performance, it is recommended that the hospital provide guidance and support in developing leadership skills and promoting work discipline among the nursing staff. Such initiatives could lead to improved outcomes in nursing services and overall hospital effectiveness.